Telaah Soal UASS Biologi Pada Siswa SMAN 8 Maros - Nurfadillah; Pertiwi Indah Lestari; Nurhidayah (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2023)
This type of research is evaluative research, namely a scientific procedure that is systematically conducted to measure the results of the program in learning according to the planned goals, by analyzing the implementation of the program that is conducted objectively. Evaluation is an activity conducted to measure the learning process of students. Exam questions used as a measuring tool must be able to provide accurate information on the abilities of students. This study aims to determine the quality of Biology test items made by biology teachers at SMAN 8 Maros. This study uses the SPSS 29 application. The results of this study indicate that the analysis of multiple-choice questions with 25 items shows a valid number of 4 questions (16%). The reliability of multiple-choice questions has a low interpretation of 0.33. Difficulty level, 11 questions (44%) are in the easy category, 13 questions (52%) are in the medium category, 1 question (4%) is in the difficult category. And 3 items (12%) had good discriminating power and 6 items (24%) had sufficient discriminating power. The number of students and the number of items also affect the analysis of the items, the more the number of students and the number of items the easier it is to analyze the level of validity, reliability, level of difficulty, and discriminating power.